1999
DOI: 10.1046/j.0909-8836.1999.eos107508.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of Bone Morphogenetic Protein‐2 and ‐3 and Osteogenic Protein‐1 during murine tooth root morphogenesis and in other craniofacial structures

Abstract: The distribution of Bone Morphogenetic Protein-2, and -3 (BMP-2 and BMP-3) and Osteogenic Protein-1 (OP-1, also known as BMP-7) during root morphogenesis and in other craniofacial structures was examined in sections of 12- to 18-d-old mouse heads using polyclonal and monoclonal antibodies. BMP-3 and OP-1 were localized in alveolar bone, cementum, and periodontal ligament, whereas BMP-2 was only localized in the alveolar bone of periodontium. All three BMPs were localized in predentine, dentine, odontoblasts, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
90
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 17 publications
1
90
0
Order By: Relevance
“…These observations suggest that this protein family may play a potential role in the development of hair follicles. BMP2, BMP4, and BMP7 have been found to be expressed in developing hair follicles (Thomadakis et al, 1999). Genetic studies confirmed that BMP signaling plays an important role in the control of cell differentiation and apoptosis (Botchkarev and Sharov, 2004).…”
Section: Introductionmentioning
confidence: 88%
“…These observations suggest that this protein family may play a potential role in the development of hair follicles. BMP2, BMP4, and BMP7 have been found to be expressed in developing hair follicles (Thomadakis et al, 1999). Genetic studies confirmed that BMP signaling plays an important role in the control of cell differentiation and apoptosis (Botchkarev and Sharov, 2004).…”
Section: Introductionmentioning
confidence: 88%
“…First, several signaling molecules such as TGFβ, BMPs, and fibroblast growth factors (FGFs) are found in the dentin matrix (Cassidy et al 1997;Roberts-Clark and Smith 2000;Thomadakis et al 1999). Therefore, a variety of biological effects arising from the dentin matrix dissolution may exist in the pulpal healing process.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Gdf7-null mutants develop abnormal cerebellar foliation (21). Although Bmp3 is expressed in the cerebellar cortical transitory zone and Purkinje cells (22), its in vivo function has not been characterized. BMP signals can transduce through Smad-dependent or Smad-independent pathways (23)(24)(25), but the exact intracellular components of BMP signaling during cerebellar development are unclear.…”
mentioning
confidence: 99%